NUTRITIONAL STATUS WITH THE SUTURE WOUND HEALING OF POSTPARTUM MOTHERS AT JETIS PUBLIC HEALTH CENTER IN YOGYAKARTA CITY - Nurul Syabin (Universitas Muhammadiyah Ponorogo, 2022)
Factors causing the puerperal infection can come from birth canal wounds which are a good medium for the growth of germs. This is caused by low maternal endurance after delivery, poor care, and poor hygiene in birth canal wounds. The purpose of this study was to determine the relationship between nutritional status and healing of perineal sutures in postpartum mothers at Jetis Health Center. This study used a cross-sectional research design. The study was conducted at the Jetis Health Center with a sample of 41 respondents and was taken by accidental sampling. The independent variable in this study was nutritional status, while the dependent variable was perineal suture healing. Data analysis using the chi-square test showed a value of p-value = 0.021 with an OR value of 5.32, meaning that mothers with poor nutritional status had a 5.3 times greater risk of experiencing perineal wound healing than mothers with good nutritional status.